ROLE OF SOCIAL MEDIA ON ENVIRONMENTAL PRACTICES (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Social media has become an important tool  for spreading knowledge and awareness on  various subjects. People are using social media  for gaining knowledge as well. Similarly  people are using social media for spreading  and gaining knowledge about environmental  related concern. Environmental concern has  become popular term with the growing world.  This research provides a brief review about uses  of social media for spreading environmental  awareness and further how these environmental  concern helps in identifying the green purchase  behaviour of the consumers. For this study,  250 questionnaires were distributed among the  respondents and 205 submitted their response.  Linear regression was applied for an analysis  of study. The results of the study show that  there is significant effect of social media on  environmental awareness and environmental  awareness on green purchase behaviour. It  means social media helps in spreading awareness  of environmental issue and concern among  individual and this awareness subsequently leads  to purchase of green product. Research study is  concluded with limitation further scope of study.
Keywords: Green purchase behaviour; Environmental awareness and concern; Social media usage; Environmental practices; Linear and Multiple Regression